The effect of hip-hop songs on fat burning through zumba exercise: Case study in “Mic Drop” by BTS as zumba accompaniment - Puput Meinis Narselina; Delya Putri Ananda (Universitas Pendidikan Indonesia, 2022)
This essay examines the correlation between hip-hop music and Zumba, with a specific focus on how the tempo of the music affects calorie burning and the overall workout experience. The study used a qualitative approach to examine the impact of participating in Zumba sessions with hip-hop genre music, namely